2020
DOI: 10.1155/2020/6928368
|View full text |Cite
|
Sign up to set email alerts
|

Chest Computed Tomography Findings in COVID-19 and Influenza: A Narrative Review

Abstract: Objective. The COVID-19 pandemic and annual influenza epidemic are responsible for thousands of deaths globally. With a similarity in clinical as well as laboratory findings, there is a need to differentiate these two conditions on chest CT scan. This paper attempts to use existing literature to draw out differences in chest CT findings in COVID-19 and influenza. Methods. A search was conducted using PubMed. 17 original studies on chest CT findings in COVID-19 and influenza were identified for full-text review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 42 publications
3
27
1
2
Order By: Relevance
“…In a review from Onigbinde et al, GGO were usually peripherally located and that vascular engorgement, pleural thickening, and subpleural lines were more frequent in COVID-19 patients. Pneumomediastinum and pneumothorax were only reported in influenza studies [ 3 ] ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a review from Onigbinde et al, GGO were usually peripherally located and that vascular engorgement, pleural thickening, and subpleural lines were more frequent in COVID-19 patients. Pneumomediastinum and pneumothorax were only reported in influenza studies [ 3 ] ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…On PubMed, 331 articles were initially found, out of which 46 articles were selected. In the end, 18 articles were selected [3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] (8 retrospective studies, 6 cohort studies, 3 casecontrol studies, 1 prospective study, 1 cross-sectional study, 1 review and meta-analysis, and 1 review) ( Figure 1 and Table 1) An outcome-free study population is first identified by the exposure/event of interest and followed in time until the outcome of interest happens. They can be prospective (carried out from the present time into the future) or retrospective (carried out at the present time and look to the past to examine medical events or outcome).…”
Section: Included Citations In the Covid-19 Vs Influenza Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the preceding statements for pneumothorax in the setting of SARS-CoV-2 infection hold true for pneumomediastinum. It is a rare entity, frequently related to mechanical ventilation, which may also appear spontaneously in the context of respiratory infections, like influenza [ 34 ]. In the series by Martinelly et al only 1 (9%) of 11 pneumomediastinum cases was labelled as spontaneous [ 5 ].…”
mentioning
confidence: 99%
“…In another study, the COVID-19 patients showed greater number of rounded opacities and interlobular septal thickenings on their chest CT scans but less pulmonary nodules, tree-in-bud opacities and pleural effusions than those with Influenza A and B pneumonias ( 20 ). Even though most CT manifestations of viral infections are nonspecific, the preliminary reports are promising about the role of chest CT images in the differentiation of pneumonias induced by COVID-19 versus those by H1N1 influenza virus ( 21 ).…”
Section: Literature Reviewmentioning
confidence: 99%